Nova's SAT prep course - Kolby, Jeff (Prep Course Ser., 2005)
Every year students pay $600 and more to test prep companies to prepare for the new SAT. Now you can get the same SAT preparation in a book. SAT prep course provides the equivalent of a two month, 50 hour course. The new SAT is challenging but it can be mastered through hard work, analytical thought, and by training yourself to think like an SAT test writer. Many of the exercises in this book are designed to prompt you to think like an SAT test writer. For example, in the SAT math section, you will find Duals. These are pairs of similar SAT problems in which only one property is different. They illustrate the process of creating SAT questions.